Vyriškojo linksniavimo paprastėjimas uteniškių tarmėje - Rinkauskienė, Regina (Baltistica, 1998)
THE SIMPLIFICATION OF THE MASCULINE DECLENSION IN THE EASTERN LITHUANIAN (UTENA) DIALECT The article deals with morphological features of the Eastern Lithuanian (Utena) dialect of the Lithuanian language. The stems of the masculine declension a, ia, u, iu are reviewed, and the causes for their interlacement are explained. The given material shows that the interlacement of stems occurs only in one direction: the non-productive u, iu stems are changed to productive a, ia stems (only separate words can be changed in the opposite way). Therefore, we come to the logical conclusion that the nouns with u, iu stems are older than adjacent a-, ia -stem forms.